OPTIMASI TEKNOLOGI PRODUKSI NANOFIBER SELULOSA BAMBU AMPEL (Bambussa vulgaris) - . Fakhruzy (Jurnal Biofisika, 2013)
Bamboo Ampel (bambussa vulgaris) is one of the lignocellulose -containing plants. Easy cultivation and a brief period of growth illustrate the potential of bamboo as a substitute for the use of synthetic fibers. Production process to produce fibers in the size of the nanofiber is the focus in this study. Semi-chemical pulping processed with NaOH done to soften and separate the cellulose fibers. Mechanical processed with disc refiner for atrial fibers (for 4, 7, 10, 13, and 16 times) do well in order to know fibrillation process optimization. Microfibrils which are formed during the ultrasonic wave treatment applied for 2 hours to change the size of the microfibrils into a nanofiber. The results of the treatment were dried with freeze dryer, and then analyzed using a scanning electron microscopy (SEM ) and X - ray diffraction ( XRD ). The results of the SEM analysis showed that the duration of mechanical processes will affect the size of the resulting cellulose microfibrils. Mechanical process 16 times, which has been treated ultrasonic , produce cellulose microfibrils with 480 nm size and crystallinity of cellulose based on the JCPDS ( ICDD ) cellulose ( C6H10O5 ) X has a monoclinic structure for a = 7.87, b = 10.31, c = 10, 13 and α = Ɣ = 90 ≠ β =122.0 , hkl values ( position crystalline cellulose ) are in the field of 002 ( 20 639 ).